Advancement in the C-H bond alkylation of (hetero)arenes catalyzed by the most abundant transition metal-iron - Pradhan, Chandini; Punji, Benudhar (Organic Chemistry Frontiers, 2024)
Alkylation reaction stands as a crucial organic transformation, fostering privileged alkylated arenes and heteroarenes in molecular science. Over the past decade, the utilization of the most abundant transition metal iron for regioselective C-H bond alkylation has gained substantial prominence, offering a straightforward and sustainable approach. Noteworthy progress has been achieved in the alkylation of diverse arenes and heteroarenes involving primary, secondary, and tertiary alkyl (pseudo)halide, alkene, and alcohol coupling partners via both the mono- and bidentate-chelate strategies. This concise and focused review provides an overview of the advancement in the iron-catalyzed alkylation of arenes and heteroarenes through step-economical C-H functionalization, their novel features, proposed mechanisms, and future research directions. The review is categorized into two major sections: (i) alkylation of arenes and (ii) alkylation of heteroarenes. Each section is discussed based on the class of arenes and heteroarenes used. Advancement in the direct C-H bond alkylation of arenes and heteroarenes using the catalysts based on the most abundant transition metal, iron, is summarized.